1,6-Conjugate-addition-induced [2+1] annulation of para-quinone methides and pyrazolones: synthesis of bis-spiro compounds with contiguous quaternary spiro-centers - Kale, Someshwar B.; Jori, Popat K.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (Organic Letters, 2019)
A diastereoselective formal 1,6-conjugate-addition-mediated [2 + 1] annulation reaction using p-quinone methides and pyrazolones has been described. The corresponding bis-spiro[cyclohexadienone-cyclopropane-pyrazolone] compounds were obtained in very good yield under mild reaction conditions.